PENGARUH LATIHAN MULTIPLE BOX TO BOX JUMPS WHIT SINGLE LEG LANDING TERHADAP POWER OTOT TUNGKAI PADA CLUB BOLAVOLI PUTRA ARWANA TAMBUSAI UTARA KABUPATEN ROKAN HULU - Sandi, Galih; Zainur, Zainur; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problems addressed in this research were when jumping and doing strokes and blocks were not optimal. This smash does not go well or can be blocked by the opponent. This research aims to determine the effect of multiple box-to-box jumps with a single leg landing on the muscle strength of the legs. The format of this research is (using a one-group pretest-post-test design approach) with a population of male volleyball players arwana Tambusai Utara, Rokan Hilir district. The data in this research is the full population of 10 individuals. The instrument used in this research was the vertical jump test which aims to determine the leg muscle strength in the sample. Then the data was statistically processed to test for normality using the Lilifours test at a significant level of 0.05α. Based on the analysis of the normality test data, X produces Lcount of 0.212 and Ltable 0.258, which means Lcount <Ltable. while variable Y produces Lcount of 0.202 and Ltable of 0.258. This means Lcount <Ltable. Based on statistical data analysis, the data is normally distributed. Based on the -t distribution test, which is 2.384 > 1.833 Tcount> Ttable data. Thus, there is an effect of multiple box-to-box jumps with single leg landing training on leg muscle strength in male volleyball players Arwana Tambusai Utara, Rokan Hilir district.Key Words: Training Multiple Box-To-Box Jumps With Single Leg Landing, Leg MuscleStrength